Giving PM-KISAN the multiplier effect - Varshney, Deepak; Kumar, Anjani; Joshi, Pramod Kumar; Roy, Devesh (Kasturi & Sons, 2020)
An IFPRI-ICAR study in UP reveals that the scheme, along with agricultural advisory services, can pull farmers out of poverty. Pradhan Mantri Kisan Samman Nidhi, popularly known as PM-KISAN, announced in December 2018 was a tectonic shift in the nature of government support to farmers in India. This scheme was aimed at addressing the liquidity constraints of farmers for meeting their expenses for acquisition of agricultural inputs and services.